2017
DOI: 10.1037/adb0000289
|View full text |Cite
|
Sign up to set email alerts
|

Review of interventions to reduce ultraviolet tanning: Need for treatments targeting excessive tanning, an emerging addictive behavior.

Abstract: Millions of Americans engage in tanning each year, defined as intentional ultraviolet radiation (UVR) exposure in the form of sunbathing or the use of indoor tanning beds. An emerging body of research suggests that UVR has addictive properties and some tanners engage in excessive tanning. This article provides an overview of the evidence of tanning addiction and a systematic review of existing tanning interventions with the goal of evaluating their potential to impact addicted tanners. Our search identified 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(29 citation statements)
references
References 82 publications
(149 reference statements)
0
29
0
Order By: Relevance
“…Although interventions aimed at affecting perceived risks and benefits of health behaviors have promising effects generally (26, 63) and in some studies of indoor tanning (61, 64), our findings suggest this approach alone may be insufficient to promote behavior change among young adults endorsing indoor tanning dependence. A recent review proposes skills-based cognitive behavioral and motivational interventions that have shown promise for addressing other behavioral addictions could be adapted to address “excessive tanning” (65). However, evidence on the design and delivery of interventions targeting young adults endorsing indoor tanning dependence, which our data indicate is characterized by frequent indoor tanning, pro-tanning beliefs, and psychiatric comorbidity, is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…Although interventions aimed at affecting perceived risks and benefits of health behaviors have promising effects generally (26, 63) and in some studies of indoor tanning (61, 64), our findings suggest this approach alone may be insufficient to promote behavior change among young adults endorsing indoor tanning dependence. A recent review proposes skills-based cognitive behavioral and motivational interventions that have shown promise for addressing other behavioral addictions could be adapted to address “excessive tanning” (65). However, evidence on the design and delivery of interventions targeting young adults endorsing indoor tanning dependence, which our data indicate is characterized by frequent indoor tanning, pro-tanning beliefs, and psychiatric comorbidity, is extremely limited.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-framed, appearance-focused messages have been shown to be effective in interventions targeting young women who tan. 7 Secondly, messages that highlight indoor tanning and skin cancer as an LGBTQ community issue by describing the disproportionate impact of indoor tanning and skin cancer on this community may be effective. This approach has been successfully used by the Truth Initiative to highlight the impact of tobacco on the LGBT community.…”
mentioning
confidence: 99%
“…Furthermore, linear regression models demonstrated that for each additional psychological symptom and problem substance, the probability of comorbid tanning addiction increased by 30% and 67%, respectively (Miller et al, 2018). Current treatment approaches for problem tanning behavior primarily aim to counsel and educate patients; however, given the association of tanning addiction with other behavioral comorbidities, future directions may aim to incorporate cognitive and behavioral based interventions (Stapleton et al, 2017).…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%